Effects of different formulations of mineral fertilizers on the agronomic parameters of maize (Zea mays) in the climate change conditions of central Benin - BATAMOUSSI, H.M.; OGA, AMOUR; SEKLOKA, E.; SAIDOU, ALIOU (My University, 2014)
In order to value the effects of different formulas of mineral manures on the agronomic parameters of maize (DMR) under climatic change conditions in the center Benin, an on farm experiment was carried out in the villages of Gome and Miniffi, respectively in the municipality of Glazoue and Dassa . The experimental design was a randomized complete block constituted of the elementary plots of 8 x 5.6 m. This design included four (04) replications and ten treatments, the different formulas of fertilizer applied: N0P0K0; N44K15K17.5; N80P30K40; N80P15K40; N80P30K25; N80P30K0; N69P30K40; N92P30K40; N69P15K25 and N46P15K25. The agronomic parameters mesured were plant growth and in circumference of the collar, the leaf area, stover and maize grains yields. The most important grain yield were obtained with the formula N80P30K40 (3.51 ± 0.23 t/ha), but N46P15K25 was more adaptable to the present agro- ecological conditions of the Center Benin.
Keywords: Zea mays; formula of manure; agronomic parameters; tropical ferruginous soils; climatic changes